Pemilihan Lampu Pada Sistem Pencahayaan Perpustakaan Menggunakan Metode Fuzzy AHP - Frisheila Sely Apriliana; Bambang Suhardi (Program Studi Teknik Industri Universitas Setia Budi, 2021)
Library is an important aspect that must exist in an educational institution because it is one source of knowledge and learning. Reading activities are the main activities carried out in the library, so the lighting aspect is one aspect that must be considered to create a good library environment. The selection of lamps as artificial light sources must be adjusted to the needs. The selection of lights can be done using the Multi Attribute Decission Making (MADM) method. One of the MADM methods used to analyze parameters and decision making criteria is Fuzzy Analytical Hierarchy Process (Fuzzy AHP). Fuzzy AHP method is the development of the AHP (Analytical Hierarchy Process) method which consists of matrix elements that are represented by fuzzy numbers. Although AHP can be used to handle quantitative and qualitative criteria in MADM, fuzzy AHP is considered able to describe vague decisions better than AHP. Besides that, Fuzzy AHP is also able to cover the subjectivity problem in AHP. In this study, the respondents are some people who are considered experts in providing judgments and decisions related to the process of selecting lights in the library. The party is the staff of the Household Section as the party in charge of administration regarding the procurement of goods in the Library, the BMN Managing staff of the electricity section as the party responsible technically about the electrical equipment in the Library and the Procurement Services Unit staff as the party responsible for procurement of goods. There are three alternative lighting brands used in this study, namely Philips, Hannoch and OSRAM. Three alternative lighting brands are used because they have a product with a lumen value that matches the lumen needs of each lamp in the Library. Based on the results of ranking using the fuzzy AHP method, it was found that the lamp chosen at priority one was Philips with a weight of 43%, priority two was OSRAM with a weight of 38%, and priority three was Hannoch with a weight of 18%.